PEMBERIAN PROGRAM LATIHAN BALLANCE EXERCISE TERHADAP KESEIMBANGAN KLIEN LANSIA DI KELURAHAN 23 ILIR PALEMBANG - Ridwan Ikop; Sulaiman; Sri Martini (Jurnal Kesehatan Saelmakers PERDANA (JKSP), 2020)
Increased morbidity cases in the elderly have caused health status problems for clients, especially theelderly. Promotive efforts through the Ballance excercise training program excerises as well as being veryimportant for clients to improve their health status. This study aims to obtain a picture of the effectivenessof Ballance Excerise on the Ballance of the body's health in the elderly. The research design used was quasiexperiment with pretest-posttest design, sampling strategy using random sampling with a sample size of 40 forthe statistical test used was the T test . found there are differences in the average before and after giving BallanceExcise with p value 0,000, there is no relationship between sex with the training program with a p value of0.351, there is no relationship between work with the training program with a p value of 0.262, there is arelationship between educational work and the training program with a p value of 0.010, there was norelationship between body weight with an exercise program with a p value of 0.735, and there was a relationshipbetween age with an exercise program with a p value of 0.006. The results can be used as a basis for policymakers and health service managers in the context of implementing complementary therapies to increasecommunity empowerment and can be replicated in various health care settings, especially in the elderly.